Clinical Efficacy and Safety of Massage for the Treatment of Restless Leg Syndrome in Hemodialysis Patients: A Meta-Analysis of 5 Randomized Controlled Trials - Xia, Min; He, Qien; Ying, Guanghui; Fei, Xiapei; Zhou, Wenjing; He, Xuelin (Frontiers in Psychiatry, 2022)
Aim: We conducted this meta-analysis to evaluate the clinical efficacy and safety of massage for the treatment of hemodialysis patients with restless leg syndrome (RLS). Methods: A comprehensive literature search was performed in PubMed, EMBASE (via OVID), and the Cochrane Library in order to identify eligible randomized controlled trials (RCTs) published before August 31, 2021. After extracted essential data and assessed risk of bias of each eligible study, we calculated the pooled estimate of RLS score and safety after treatment. Statistical analysis was performed by using Review Manager 5.3. Results: Five studies involving 369 hemodialysis patients with RLS were analyszd. The RLS score after treatment (mean difference [MD], -12.01; 95% confidence interval [CI], -14.91 to -9.11) and mean difference of RLS score at the beginning and end of treatment (mean difference [MD], -11.94; 95% confidence interval [CI], -15.45 to -8.43) in massage group was significantly better than that in route care group. Subgroup analysis suggested that massage with lavender oil was also significantly reduced the RLS score after treatment (mean difference [MD], -14.22; 95% confidence interval [CI], -17.81 to -10.63) and mean difference of RLS score at the beginning and end of treatment (mean difference [MD], -14.87; 95% confidence interval [CI], -18.29 to -11.45) compared with route care. Meanwhile, massage regime significantly relieved RLS severity compared with route care, but not increased adverse events. Conclusions: Massage may be a preferred treatment modality for hemodialysis patients with RLS because it effectively reduces RLS symptoms, relieves RLS severity, and does not increase the risk of adverse events. However, future study with a larger sample size is warranted due to the fact that only limited number of eligible studies with small sample size are enrolled.